Intermediate pyrolysis of Ficus nitida wood in a fixed-bed reactor: effect of pyrolysis parameters on bio-oil and bio-char yields and properties - Tabal, Amine; Belyazid, Oumayma; Dahman, Hicham; Berrich, Emna; Jeguirim, Mejdi; El Achaby, Mounir; El Harfi, Khalifa; Aboulkas, Adil (Comptes Rendus. Chimie)
This study aims to investigate the influence of various operating conditions on the conversion of Moroccan woody biomass using pyrolysis process. The pyrolysis reaction was performed at 350, 400, 450, 500, 500, 550, and 600 °C, for different heating rates of 20, 50, 80, and $100~\text{°}C{· }min^{-1}$, and under flow rates of N$_2$ of 50, 100, 200, 400, and $800~mL{· }min^{-1}$. The oil yield of 41.85% was found maximum at the following optimal conditions: a temperature of 500 °C, a heating rate of $100~C{· }min^{-1}$ and a N$_2$ flow rate of $100~mL{· }min^{-1}$. The composition and characteristics of bio-oil and bio-char were determined by elemental and proximate analysis, GC–MS, NMR, FTIR, ATG, BET and SEM. Thermogravimetric analysis revealed that a 39% conversion of the bio-oil is in the medium naphtha range. High quantity of aliphatic, phenolic ketones and aromatic groups are present in the bio-oil, which underlines the need for further upgrading for the bio-oil to be considered as a potential biofuel and valuable chemical product. The physicochemical properties of biochar show that it is a material with a high calorific value and a high percentage of carbon relative to raw biomass. Thus, it can be used as promising material in various application such as activated carbon synthesis and biofertilizers.